Comparative Study of Alum and Moringa Oleifera Seed Powder in Turbidity Removal from River Water and Synthetic Solution (Kaolin) - Naveendre Vel; Nor Hazren Binti Abdul Hamid (Progress in Engineering Application and Technology, 2025)
As the global population continues to rise, the demand for clean water has been growing, making water pollution and its attendant dangers, such as turbidity, a key issue in developing countries. Alum and other conventional coagulants are to help reduce turbidity but also threaten the environment and human health by becoming toxic and creating sludge. One of the objectives of this study was to assess the effectiveness of Moringa Oleifera seed powder, a natural coagulant, in the removal of turbidity from water in comparison with Alum, which is a commonly used coagulant in water treatment. Thus, the study determines the best working conditions such as pH, dosage and settling time of coagulant. Water quality parameters such as turbidity, pH and others were used to evaluate the effectiveness of coagulants in water treatment, through experiments carried out with a synthetic kaolin suspension and a natural river water sample. To characterise the chemical structure of Moringa Oleifera seed powder and verify its physical properties, Fourier Transform Infrared Spectroscopy (FTIR) & Field Emission Scanning Electron Microscopy (FESEM) were analysed. Our results showed that Moringa Oleifera effectively reduced turbidity, achieving comparable or higher results than those obtained with Alum. On top of that, Moringa Oleifera produced almost no sludge, making it a more environmentally friendly option. The finding of this study provides information that Moringa Oleifera is an effective, cheap and environmentally friendly coagulant, and this may be a potential solution for areas with difficulties accessing chemical coagulants for water treatment. These results underscore the potential of natural coagulants as a low-cost solution to improve water quality in underdeveloped areas.